Comprehensive investigation of geometrical parameters utilizing various XRD methods and their impact on the electrochemical performance of SnS2 nanoparticles - Kalpana, S.; Dar, Mohd Arif; Fareed, S. Sheik; Arularasan, P. (Indian journal of physics, 2024)
In this paper, SnS 2 nanoparticles (NPs) are prepared by the solvothermal method using tin chloride, thiourea and sodium hydroxide as precursors. The SnS 2 NPs were characterized through different experimental techniques. The X-ray diffraction (XRD) confirmed the hexagonal crystal structure of SnS 2 NPs. The Crystallite size (D) of SnS 2 NPs is determined by the Debye–Scherrer method, Williamson–Hall (W–H) method, Size–Strain (SS) method and Halder–Wagner (H–W) method. The Scanning electron microscopy (SEM) and high-resolution transmission electron microscopy (HRTEM) show clear spherical morphology. The direct energy band gap of SnS 2 NPs are 2.0 and 1.7 eV, respectively. Through cyclic voltammetry (CV) and galvanostatic charging/discharging (GCDs) studies, the SnS 2 electrodes have Specific capacitance (Cp) of 622 and 848 (F/g) at the scan rate of 10 mV/s and 625 and 683 (F/g) at the current density (CD) of 5 mA, respectively. The SnS 2 electrodes have specific energy (SE) of 32 and 35 (Wh/kg) at a specific power (SP) of 1500 (W/kg), respectively.